A ball for Daisy - Raschka, Christopher (New York : Schwartz & Wade Books, 2011)
Daisy the dog is heartbroken when her favorite toy ball is destroyed while she is playing with another dog, but she realizes she has gained something, too.
Caldecott Medal/Honor
Notable/Best Books (A.L.A.)
School Library Journal starred
Booklist, June 2011
Horn Book Starred, September 2011
Horn Book, April 2012
Keywords: Balls (Sporting goods) -- Juvenile fiction; Dogs -- Juvenile fiction; Balls (Sporting goods) -- Fiction; Dogs -- Fiction; Stories without words; Balls (Sporting goods) -- Fiction; Dogs -- Fiction; Stories without words; Picture books for children